2019
DOI: 10.1016/j.omtm.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and MR-Based Monitoring of AAV9 Vector Delivery into Cerebrospinal Fluid of Nonhuman Primates

Abstract: Here we evaluated the utility of MRI to monitor intrathecal infusions in nonhuman primates. Adeno-associated virus (AAV) spiked with gadoteridol, a gadolinium-based MRI contrast agent, enabled real-time visualization of infusions delivered either via cerebromedullary cistern, lumbar, cerebromedullary and lumbar, or intracerebroventricular infusion. The kinetics of vector clearance from the cerebrospinal fluid (CSF) were analyzed. Our results highlight the value of MRI in optimizing the delivery of infusate int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 38 publications
3
32
1
Order By: Relevance
“…In the GLD dog, we evaluated the efficacy of intrathecal administration of AAV9-cGALC in both presymptomatic and symptomatic dogs. Vector was administered at the cisterna magna, since we and others have shown that intracisternal AAV9 administration is safe in cats, dogs, and nonhuman primates and results in up to 100-fold more efficient gene transfer to the brain than does administration via lumbar puncture (27) or intravenously (20). Intracisternal AAV9 is currently being administered to patients with mucopolysaccharidosis I (NCT02362438) and GM1 gangliosidosis (NCT04273269) in clinical trials, making this a clinically relevant route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…In the GLD dog, we evaluated the efficacy of intrathecal administration of AAV9-cGALC in both presymptomatic and symptomatic dogs. Vector was administered at the cisterna magna, since we and others have shown that intracisternal AAV9 administration is safe in cats, dogs, and nonhuman primates and results in up to 100-fold more efficient gene transfer to the brain than does administration via lumbar puncture (27) or intravenously (20). Intracisternal AAV9 is currently being administered to patients with mucopolysaccharidosis I (NCT02362438) and GM1 gangliosidosis (NCT04273269) in clinical trials, making this a clinically relevant route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…The simplest route of drug injection into CSF is a lumbar puncture. However, MRI studies in the primate show this route of delivery may treat the surface of the spinal cord, but very little drug reaches the cerebral hemispheres (Ohno et al, 2019). An alternative route of CSF injection is intra-cerebroventricular (ICV) delivery following the implantation of an Ommaya reservoir into one of the two LVs (Ommaya, 1963).…”
Section: Different Routes Of Drug Injection Into Csf: Lumbar Ventricmentioning
confidence: 99%
“…Apart from rapid drug delivery to the peripheral bloodstream, other limitations of the Ommaya reservoir include the poor distribution of the drug to the contralateral side of the brain, owing to minimal retrograde flux of CSF from the 3rd ventricle to the opposite LV (discussed below). The third route of CSF injection that achieves the best distribution of drugs to both the bilateral forebrain and the spinal cord is a cisternal injection in the cerebro-medullary cistern (CMC; Ohno et al, 2019). However, this route of injection is technically difficult, is near vital structures of the brain, and has yet to enter into clinical practice.…”
Section: Different Routes Of Drug Injection Into Csf: Lumbar Ventricmentioning
confidence: 99%
“…An extensive study conducted by Ohno et al compared the kinetics of vector clearance from the CSF following infusion of AAV vectors to the lumbar cistern and the cerebromedullary cistern, or cisterna magna (CM) in NHPs [ 251 ]. This and other studies demonstrated that administration via suboccipital puncture to the cisterna magna is remarkably efficient in widely transducing the brain and spinal cord in NHPs [ 252 , 253 ].…”
Section: In Vivo Gene Therapymentioning
confidence: 99%